"Ay, nosebleed!": Negotiating the place of English in contemporary Philippine linguistic life. (January 2018) - Osborne, Dana
Abstract: This article describes and analyzes the form and function of the term 'nosebleed' as it is used by speakers in the contemporary Philippine linguistic scene. 'Nosebleed' operates as a metapragmatic, semiotic stance marking device used to bracket various kinds language/s in relation to concepts of high sociocultural value in the archipelago: local concepts of the commensurability of language- and person-types, and culturally-enregistered joking styles that mitigate hiya, or 'shame' in interaction. This analysis draws from popular discourses to outline the ideological foundations of the term and goes on to examine its social and linguistic effects to theorize the ways that homegrown metapragmatic tools such as 'nosebleed' can shape varieties of language over time. Highlights: 'Nosebleed' is a metapragmatic semiotic stance-marking tool used to negotiate the role of English in everyday interactions in the Philippines. Culturally-enregistered modes of interaction sustain linguistic diversity in the Philippines. 'Nosebleed' taps into salient local concepts of the commensurability of language-, body- and person-types. Popular discourses and local uses are contrasted to highlight the semiotically open-ended complexity of 'nosebleed' in the contemporary Philippine linguistic scene.